2023
DOI: 10.1111/jwas.12969
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the physiological responses of Pacific abalone (Haliotis discus hannai) to various stressors to identify a suitable stress indicator

Abstract: The Pacific abalone (Haliotis discus hannai) is the most economically valuable shellfish species in Northeast Asia, accounting for most of the shellfish production in South Korea. Despite the continuous improvement in the productivity of domestic abalone aquaculture, rapid seawater temperature changes caused by global warming have led to mass mortality in coastal abalone farms. Therefore, research on environmental stressors is urgently needed to prevent abalone production losses. This study analyzed the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Abalones exposed to high‐temperature stress activate HSP mechanisms to prevent protein damage, assist in antioxidant responses, and prevent stress (Boopathy et al, 2022). Lee et al (2023) reported a significant increase in HSP70 mRNA expression in the muscle of disk abalones exposed to 28°C. In our study, HSP70 mRNA expression in the 28°C high‐temperature experiment was higher compared with that in the 20°C experiment, suggesting that abalones exposed to high‐temperature conditions activated the HSP70 mechanism as part of their internal stress mitigation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Abalones exposed to high‐temperature stress activate HSP mechanisms to prevent protein damage, assist in antioxidant responses, and prevent stress (Boopathy et al, 2022). Lee et al (2023) reported a significant increase in HSP70 mRNA expression in the muscle of disk abalones exposed to 28°C. In our study, HSP70 mRNA expression in the 28°C high‐temperature experiment was higher compared with that in the 20°C experiment, suggesting that abalones exposed to high‐temperature conditions activated the HSP70 mechanism as part of their internal stress mitigation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In South Korea, abalone aquaculture production reached 23,199 tons in 2021, accounting for 30% of the country's shellfish production [21]. As abalone aquaculture relies entirely on hatchery-produced seed, understanding the reproductive behavior and regulation of abalone is crucial for successful seed production.…”
Section: Introductionmentioning
confidence: 99%